Electrocorticography of Spatial Shifting and Attentional Selection in Human Superior Parietal Cortex - Schrooten, Maarten; Ghumare, Eshwar G.; Seynaeve, Laura; Theys, Tom; Dupont, Patrick; Van Paesschen, Wim; Vandenberghe, Rik (Frontiers in Human Neuroscience, 2017)
Spatial-attentional reorienting and selection between competing stimuli are two distinct attentional processes of clinical and fundamental relevance. In the past, reorienting has been mainly associated with inferior parietal cortex. In a patient with a subdural grid covering the upper and lower bank of the left anterior and middle intraparietal sulcus (IPS) and the superior parietal lobule (SPL), we examined the involvement of superior parietal cortex using a hybrid spatial cueing paradigm identical to that previously applied in stroke and in healthy controls. In SPL, as early as 164 ms following target onset, an invalidly compared to a validly cued target elicited a positive event-related potential (ERP) and an increase in intertrial coherence (ITC) in the theta band, regardless of the direction of attention. From around 400–650 ms, functional connectivity [weighted phase lag index (wPLI) analysis] between SPL and IPS briefly inverted such that SPL activity was driving IPS activity. In contrast, the presence of a competing distracter elicited a robust change mainly in IPS from 300 to 600 ms. Within superior parietal cortex reorienting of attention is associated with a distinct and early electrophysiological response in SPL while attentional selection is indexed by a relatively late electrophysiological response in the IPS. The long latency suggests a role of IPS in working memory or cognitive control rather than early selection.